Statistical supplement 1961: tin tinplate canning - International Tin Council (London : International Tin council, 1961)
The purpose of this 1961 Statistical Supplement is to keep up-to-date the basic information on the tin, tinplate, tin alloy and canning industries which are treated in detail in the Statistical Year Book.
rpm 15/02/2019
Ref
Keywords: Statistical Supplement